2018
DOI: 10.1007/s10517-018-4088-8
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Increases Viability of Neurons in Rat Cerebral Cortex and Normalizes Bax/Bcl-2 Ratio under Conditions of Oxidative Stress

Abstract: We studied the protective effect of insulin in various concentrations and its effect on the Bax/ Bcl-2 ratio in neurons of rat cerebral cortex under conditions of oxidative stress. The protective effect of insulin was dose-dependent within the nanomolar range (1 nM<10 nM<100 nM). Preincubation with insulin in concentrations of 100 nM and 1 μM significantly increased Bcl-2 content in neurons in 5, 30, and 45 min and 1, 2, and 4 h after the start of cell exposure to HO. This prooxidant increased the Bax/Bcl-2 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Many studies have confirmed that NGS technology can improve the diagnosis of chromosomal abnormalities. 31 , 32 CNV‐seq is a genomic copy number variation detection technology based on low‐depth whole‐genome sequencing. CNV‐seq can detect CNVs of different sizes by adjusting the sequencing depth and changing the resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed that NGS technology can improve the diagnosis of chromosomal abnormalities. 31 , 32 CNV‐seq is a genomic copy number variation detection technology based on low‐depth whole‐genome sequencing. CNV‐seq can detect CNVs of different sizes by adjusting the sequencing depth and changing the resolution.…”
Section: Discussionmentioning
confidence: 99%
“…The proteins of the BCL-2 family are the most important regulators of mitochondria-related apoptosis. The ratio of pro- and antiapoptotic proteins (BCL2 and Bax) determines whether mitochondria initiate the cell death program by releasing cytochrome C and other proapoptotic factors [ 22 ]. There was no significant difference in the number of TUNEL-positive cells or in the expression of BCL2, Bax, and cleaved-caspase-3 between the H 2 O 2 , overexpression vector, and knockdown vector groups ( P > 0.05, Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…99 As part of these role, it streamlines cellular energy production and health in a variety of ways. It opposes oxidative stress by promoting GSH synthesis, 152,153 opposes with GSH the apoptosis-promoting effects of H2O2, 154 acts as an anti-inflammatory agent in the immune system, 155 promotes mitochondria health, oxidative phosphorylation, ATP production, and protein synthesis, 156,157 promotes synaptic plasticity, 158 and opposes calcium overload and toxicity. [159][160][161][162][163][164][165][166] Insulin promotes the production of N-Acetylglucosamine (GlcNAc), 167 whose use in O-GlcNAcylation decreases intracellular Ca 2+ load, 168 H2O2 production, and permeability pore opening.…”
Section: Insulin Protection In Alsmentioning
confidence: 99%